Implementasi Kebijakan Kota Layak Anak (KLA) Klaster Perlindungan Khusus dalam Pencegahan Kekerasan Anak di Kota Padang - Salma Awalun Nissa; Jumiati (YASIN, 2026)
Violence against children remains a serious problem in the implementation of the Child-Friendly City (KLA) initiative, particularly within the Special Protection Cluster. Although the Padang City Government has implemented various programs and services to prevent violence against children, the incidence of such violence remains high and has even increased following the enactment of the Regional Regulation on KLA. This study aimed to analyze the implementation of the KLA Policy for the Special Protection Cluster in preventing violence against children in Padang City and to identify the supporting and inhibiting factors affecting its implementation. The study employed a descriptive qualitative approach using George C. Edwards III’s policy implementation framework, which encompasses the dimensions of communication, resources, disposition, and bureaucratic structure. The results showed that policy communication had been conducted through school-based dissemination activities and outreach by Community-Based Integrated Child Protection (PATBM) cadres, but its coverage remained uneven. The availability of resources was still limited, particularly in terms of personnel and funding, whereas the disposition dimension indicated a high level of commitment among field-level implementers. In the bureaucratic structure dimension, interagency coordination through the KLA Task Force had been established, but its technical authority remained limited. Uneven policy communication, limited implementation resources, low public awareness, and a weak program evaluation system were the main factors hindering the effectiveness of efforts to prevent violence against children. This study concludes that the implementation of the KLA Policy for the Special Protection Cluster in Padang City has not yet been optimal. The findings emphasize the need to strengthen resource capacity, improve public literacy, expand the reach of policy communication, and develop an evaluation system based on measurable indicators to enhance the effectiveness of child protection.